Fungsi Orang Tua dalam Mendukung Keberhasilan Belajar Anak di Pendidikan Anak Usia Dini (PAUD) Melati 08 Jakarta Timur - Putra Wicaksono, Mahendra Fahri; Hoerniasih, Nia; Pujiarto, Pujiarto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to describe the functions of parents in supporting children's learning success at PAUD Melati 08 Jakarta Timur, identify the supporting factors that enable parents to assist in the learning process, and explain the outcomes of parental functions in the success of early childhood education at PAUD Melati 08. The research employed a qualitative approach with a case study method. Data collection techniques included observation, interviews, and documentation. The research stages consisted of orientation, exploration, and member checking. Data analysis techniques involved data collection, data reduction, data presentation, and verification. The findings revealed that parents at PAUD Melati 08 performed their roles in various ways, such as maintaining active communication with children, providing emotional support, and assisting the learning process at home. Several factors supported parental involvement, including adequate educational background, stable family economic conditions, and a strong understanding of the importance of parental roles in children's education. This study concludes that parental involvement significantly contributes to children's learning success at PAUD Melati 08 Jakarta Timur. Children who receive consistent attention and support from their parents demonstrate more stable cognitive, motor, language, and emotional development. Keywords: Parental function, Learning success, PAUD